Cover Feature: Thermal Decomposition of Ternary Sodium Graphite Intercalation Compounds (Chem. Eur. J. 29/2020). Issue 29 (23rd April 2020) - Au, Heather; Rubio, Noelia; Buckley, David J.; Mattevi, Cecilia; Shaffer, Milo S. P.
Abstract : Graphite Intercalation compounds (GICs) are often used to produce exfoliated or functionalized graphene related materials in a specific solvent. The bulk of the intercalation compound is stable under ambient conditions, trapped between the graphene layers. However, heating drives a reorganization of the sodium and associated solvent molecules, leading to the step‐wise evaporation of the solvent. More information can be found in the Full Paper by M. S. P. Shaffer et al. on page 6545 .